2023
DOI: 10.1093/ornithapp/duad041
|View full text |Cite
|
Sign up to set email alerts
|

Sixty-years of community-science data suggest earlier fall migration and short-stopping of waterfowl in North America

Amelia R Cox,
Barbara Frei,
Sarah E Gutowsky
et al.

Abstract: Worldwide, migratory phenology and movement of many bird species is shifting in response to anthropogenic climate and habitat changes. However, due to variation among species and a shortage of analyses, changes in waterfowl migration, particularly in the fall, are not well understood. Fall migration phenology and movement patterns dictate waterfowl hunting success and satisfaction, with cascading implications on economies and support for habitat management and securement. Using 60 years of band recovery data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 116 publications
(185 reference statements)
1
16
0
Order By: Relevance
“…In our study (Gaget et al (2024), we found that ducks contribute less than other species to waterbird community adjustment to climate warming. The main hypothesis was that hunting-oriented management may increase the site fidelity of hunted species and thus reduce their distribution change.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…In our study (Gaget et al (2024), we found that ducks contribute less than other species to waterbird community adjustment to climate warming. The main hypothesis was that hunting-oriented management may increase the site fidelity of hunted species and thus reduce their distribution change.…”
mentioning
confidence: 53%
“…We thank Santangeli (2024) and Navedo (2024) for promoting discussion and brainstorming around the conclusions of our paper (Gaget et al, 2024).…”
mentioning
confidence: 99%
See 3 more Smart Citations